Social Osmosis and Patterns of Crime - Sah, Raaj K. (Journal of Political Economy, 1991)
Crime and the fear of crime have a deep negative impact on personal and societal well-being. Several observed patterns regarding criminal behavior, however, remain inadequately understood. In this analysis, individual's perceptions (concerning their probabilities of punishment) and choices are determined endogenously, while incorporating the information available to them and how this information is generated within the economy. The resulting dynamic relationships are then studied to examine how criminality might evolve over time, why crime participation rates might differ among societal groups even when they face similar economic fundamentals, and how the features of the economy might affect these rates.